The Use of Peppermint Oil in Gastroenterology - Scarpellini, Emidio; Broeders, Bert; Schol, Jolien; Santori, Pierangelo; Addarii, Mariachiara; Boccuto, Luigi; Carbone, Florencia; Abenavoli, Ludovico; Tack, Jan (Current Pharmaceutical Design, 2023)
Background: For decades, mint has been used worldwide for its relieving effects against gastrointestinal disturbances. Peppermint is a perennial herb common in Europe and North America. The active ingredient of peppermint oil is menthol and has various gastroenterological and non-gastroenterological uses, especially in the context of functional gastrointestinal disorders (FGIDs). Methods: We conducted a literature search on the main medical databases for original articles, reviews, meta-analyses, randomized clinical trials, and case series using the following keywords and acronyms and their associations: peppermint oil, gastro-intestinal motility, irritable bowel syndrome, functional dyspepsia, gastrointestinal sensitivity and gastrointestinal endoscopy. Results: Peppermint oil and its constituents exert smooth muscle relaxant and anti-spasmodic effects on the lower esophageal sphincter, stomach, duodenum, and large bowel. Moreover, peppermint oil can modulate visceral and central nervous system sensitivity. Taken together, these effects suggest using peppermint oil both for improved endoscopic performance and for treating functional dyspepsia and irritable bowel syndrome. Importantly, peppermint oil has an attractive safety profile compared to classical pharmacological treatments, especially in FGIDs. Conclusion: Peppermint oil is a safe herbal medicine therapy for application in gastroenterology, with promising scientific perspectives and rapidly expanding use in clinical practice.
Keywords: gastrointestinal motility